2014
DOI: 10.1186/bf03351787
|View full text |Cite
|
Sign up to set email alerts
|

Deep seismic reflection experiment using a dense receiver and sparse shot technique for imaging the deep structure of the Median Tectonic Line (MTL) in east Shikoku, Japan

Abstract: A seismic experiment was carried out in east Shikoku, Japan, to detect deep reflections across the Median Tectonic Line (MTL), which juxtaposes low-P/T metamorphic rocks with high-P/T metamorphic rocks. Our experiment employed an unconventional technique: sparse shot spacing, a strong energy source (dynamite) and a dense array of seismometers. The above specifications produce only single fold coverage without common midpoint (CMP) stacking. Nevertheless, the reflection profile provides essential information on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 10 publications
2
15
0
Order By: Relevance
“…Ito et al (1996) found a sharp reflector dipping [30][31][32][33][34][35][36][37][38][39][40] • north in the upper crust by a seismic reflection survey. Kawamura et al (2003) and Sato et al (2005) also found that the sharp reflector extended to the lower crust from a recent seismic explosion survey. Although the subsurface structures in these regions have become clearer by analyzing geophysical data, the relations among the structures or between the structures and hypocenter distributions are not still clear.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Ito et al (1996) found a sharp reflector dipping [30][31][32][33][34][35][36][37][38][39][40] • north in the upper crust by a seismic reflection survey. Kawamura et al (2003) and Sato et al (2005) also found that the sharp reflector extended to the lower crust from a recent seismic explosion survey. Although the subsurface structures in these regions have become clearer by analyzing geophysical data, the relations among the structures or between the structures and hypocenter distributions are not still clear.…”
Section: Introductionmentioning
confidence: 98%
“…Although the clear R1 cells in this study locate at similar depths to the oceanic Moho discontinuity, it seems improbable that they correspond to the obscure reflectors of Kurashimo et al (2002). Kodaira et al (2002) pointed out the existence of water at the PHS plate boundary by analyzing reflected phases with large amplitudes recorded in an onshore-offshore deep seismic survey conducted in the western Nankai Trough seismogenic zone, and estimated the very thin layer (about 300 m) with very low velocity at the plate boundary. Kurashimo et al (2002) also suggested a very low velocity layer with 1 km thickness at the upper most part of the PHS slab obtained from the same waveform calculation for very clear reflected phases as Kodaira et al (2002).…”
Section: Relation Of Slab To Subcrustal Earthquakes In East-mentioning
confidence: 99%
See 1 more Smart Citation
“…Developing the correct processes and selecting the correct parameters based on the characteristics of the data from the large dynamite shots are the key to imaging the lower crust and Moho. Many geophysicists have achieved good results in processing data from dynamite shots (e.g., Levander et al 1994;Klemperer et al 1986;Kawamura et al 2003;Stern et al 2015).…”
Section: Acquisition and Analysis Of Seismic Datamentioning
confidence: 99%
“…For example, Klemperer et al (1986) determined the structure of the Moho in Nevada, USA, using large dynamite shots. Kawamura et al (2003) revealed the deep crustal structure of the eastern central tectonic line using two large dynamite shots. Stern et al (2015) determined the structure of the Moho and the lithosphere-asthenosphere boundary beneath North Island, New Zealand, using large dynamite shots.…”
Section: Introductionmentioning
confidence: 99%